MADRASAH LEADERSHIP IN IMPLEMENTING CHARACTER EDUCATION BASED ON THE 2013 CURRICULUM IN THE COVID-19 PANDEMIC PERIOD AT MADRASAH ALIYAH IN THE CITY OF SEMARANG - Ruba'i, Sari Hernawati (Proceeding Of The International Seminar and Conference on Global Issues, 2020)
ABSTRACTEducation is indeed something that is very important, because it consists of instilling character through efforts to internalize learning, even in the midst of the Covid-19 pandemic. For this reason, researchers are interested in conducting research at madrasahs in Semarang City with the formulation of the problem: How is the concept of leadership in Islam, the leadership of the madrasah principal, obstacles and solutions to the problem of madrasah leadership in implementing character education based on the 2013 Curriculum during the Covid-19 pandemic in Semarang City This research is a field research, with the type of qualitative research. With a descriptive approach, this research uses interview, observation and documentation data collection techniques. The analysis technique uses descriptive analysis-analysis. Based on the analysis and discussion, this study produced several research findings, first; Leadership in Islam is understood as an abilityleaders to foster good relations, communication and interaction with subordinates and all elements within an organization. Second; the leadership of the madrasa head in the implementation of character education based on the 2013 Curriculum in the futurethe Covid-19 pandemic in Semarang City, among others, is the type of democratic leadership, which includes participatory and deliberative attitudes; and the transformational paternalist leadership type, namely the fatherly leader type, high affection for subordinates, but instead provides many opportunities for subordinates, encouraging and supporting them to be more creative-innovative. Third; obstacles to madrasa heads in implementing character education based on the 2013 Curriculum during the Covid-19 pandemic in Semarang City, namely (1) constraints on the limitations of student online learning tools, (2) low student participation in learning, (3) absorption of teaching material which is only 50% , which is due to the ineffectiveness of learning with an online/online system. Fourth; solution for the leadership of the madrasa head in the implementation of character education based on the 2013 Curriculum during the Covid-19 pandemic in Semarang City, namelycarrying out monitoring, coaching and evaluation activities in madrasas, (2) establishing communication with parents of students, (3) carrying out the development of superior madrasah programs.Keywords: Leadership, Madrasa Head, Character Education, Curriculum 2013, Covid-19 Pandemic